Isolation and Molecular Identification of Endophytic Fungi Associated with Brown Algae for Inhibiting Escherichia coli ESBL - Wiradana, Putu Angga; Permatasari , Anak Agung Ayu Putri; Sari, Ni Kadek Yunita; Widhiantara, I Gede; Sandhika, I Made Gde Sudyadnyana; Waruwu, Ernawati; Fimaputra, Jatu Maranatha; Panjaitan, Novaria Sari Dewi; Putri, Fadillaisyia Riandani; Ansori, Arif Nur Muhammad
Background: The marine environment is the main source of research on natural products in the future. In addition, marine microorganisms have been identified as a natural source capable of developing new antibiotic compounds, including controlling urinary tract infections caused by Escherichia coli ESBL. Purpose: This study aims to isolate, select, and test the potential of brown macroalgae endophytic fungi (Phaeophyceae) collected from the coastal waters of Sanur, Bali Province. Methods: Three types of brown algae were collected from Sanur Beach and their endophytic fungi were isolated using PDA media. Antibacterial activ